Penggunaan pendekatan saintifik untuk meningkatkan kemampuan menyelesaikan soal hots pada materi karakteristik geografi Indonesia - Vellen Pradana; Jenny Indrastoeti Siti Poerwanti; Siti Wahyuningsih (Universitas Sebelas Maret, 2020)
This research have a purpose to improve the ability of HOTS problem solving in the material of characteristic of Indonesian geography by using saintific approach. The type of research is classroom action research, that have two cycles. The subject of this research ware student of the 5th student at Tegalsari No.60 elementary state school Surakarta in the 2019/2020 years of academic. There are 30 students totally. Data collection techniques of this research are interview, test, observation, and documentation with triangulation and content validity as a data analisis. 50% of classical completeness is obtained in the first cycle. In the second cycle, the result of classical completeness is 80%. Conclusions based on the result of the study ware the ability of HOTS problem solving in material characteristic of Indonesian geography on 5th students at Tegalsari No.60 elementary state school Surakarta in the 2019/2020 years of academic can be improved by using saintific approach. This research is expected to improve the learning process on the material characteristics of Indonesian geography related to maximizing the ability to think at a higher level by using scientific reasoning.